Polycarbonate composite article

KR103034800B1Active Publication Date: 2026-10-21COVESTRO DEUTSCHLAND AG
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
KR1020227035367
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-05-11
Filing Date
2021-04-09
Publication Date
2026-10-21
Estimated Expiration
2041-04-09

Smart Images

  • Figure 112022106972845-PCT00004_ABST
    Figure 112022106972845-PCT00004_ABST
Patent Text Reader

Abstract

The present application relates to a polycarbonate composite article, a method for manufacturing the same, and uses the same. The polycarbonate composite article comprises a foamed polycarbonate layer and a non-foamed polycarbonate film layer on the foamed polycarbonate layer. The polycarbonate composite article according to the present invention has reduced weight and improved signal penetration performance and can be used as an antenna housing.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention belongs to the field of polymer composites. Specifically, the present invention relates to a polycarbonate composite article particularly suitable for antenna housings, a method of manufacturing the same, and the use of the same. Background Technology

[0002] 5G technology is the upcoming fifth-generation wireless mobile communication technology. 5G wireless networks will support a 1,000-fold increase in capacity, connections for at least 10 billion devices, and a 10 Gb / s individual user experience capable of extremely low latency and response times. 5G is the backbone for artificial intelligence (AI), the Internet of Things (IoT), automation, connected cars, telemedicine, smart cities, and more. The deployment of these networks is expected to occur between 2020 and 2030.

[0003] Unlike 4G technology, 5G technology will employ active antenna units [AAU] rather than passive antenna units. The design of active antennas substantially increases the weight of the final antenna components. Considering the load weight of the pole, the stability of the antenna under strong winds, and high installation and maintenance costs, reducing the weight of active antennas becomes particularly important, especially for macro base station antennas where the component size is considerably large. Additionally, dimensional stability is also important due to the large size of the antenna housing.

[0004] 5G can cover a wide range of waves, including mid-band frequencies below 6 GHz and millimeter waves above 24 GHz. Due to the high attenuation of these high-frequency electromagnetic waves when they encounter obstacles during transmission, high signal transmission will be one of the key requirements for antenna protection materials used in 5G technology.

[0005] Excellent signal transmission performance means that the dielectric constant Dk and loss factor Df of the material are low and stable over a wide range of frequencies and environmental conditions. When the antenna housing has a two-layer or multi-layer structure, S11 (reflection loss) and S21 (gain) are indicators commonly used to characterize the transmission performance of the antenna, and their units are in dB.

[0006] There are several patent documents regarding antenna housings. For example, US4896164 describes a conventional tuned layered antenna housing structure (Fig. 2) in which an inner layer and an outer layer of a polyester resin / E-grade glass (glass fiber) laminate are placed on the front and rear surfaces, respectively, of a rigid polyimide foam, and a specific thickness selected for conventional reflection elimination is present. Although the tuned layered antenna housing structure has significantly improved broadband characteristics in terms of insertion loss and reflection loss, the insertion loss is minimal at 36 GHz in the range of 6 to 42 GHz, and the tuned structure cannot be effectively used beyond two narrow bandwidths (8 to 12 GHz) and (27 to 31 GHz).

[0007] US2018 / 0241119 describes a multi-wall radar antenna shield that not only provides high penetration of microwave signals but also protects the antenna shield from threats from aircraft. However, due to the complexity of the composite system and the multi-layer / multi-wall, the composite system of the entire antenna housing is more complex. Similarly, the tuned structure cannot be effectively used beyond two 4 kHz narrow bandwidths (8 to 12 kHz and 26 to 30 kHz).

[0008] Therefore, in 5G-related applications, there is still a need for antenna housings with improved signal penetration performance, dimensional stability, and lightweight properties.

[0009] Accordingly, the objective of the present invention is to provide an antenna housing having improved signal penetration performance, dimensional stability, and lightweight properties.

[0010] Another objective of the present invention is to provide a method for manufacturing an antenna housing.

[0011] According to the first aspect of the present invention,

[0012] Opaque expanded polycarbonate layer; and

[0013] Non-foamed polycarbonate film layer on foamed polycarbonate layer

[0014] Includes,

[0015] Here

[0016] The expanded polycarbonate layer comprises polycarbonate resin, an impact modifier, and an optional flame retardant, and

[0017] The non-foamed polycarbonate film layer comprises a polycarbonate resin and an optional UV stabilizer, and has a thickness of 0.2 to 1.00 mm;

[0018] The ratio of the thickness of the non-foamed polycarbonate film layer to the thickness of the foamed polycarbonate layer is in the range of 1:3 to 1:20;

[0019] A polycarbonate composite article is provided that does not contain an inorganic reinforcing material.

[0020] According to a second aspect of the present invention,

[0021] A step of placing a non-foamed polycarbonate film on the inner surface of an injection mold and closing the mold to form a cavity; and

[0022] A step of forming a foamed polycarbonate layer by injecting and foaming a molten polycarbonate composition comprising a polycarbonate resin, an impact modifier, and an optional flame retardant in a cavity.

[0023] A method for manufacturing a polycarbonate composite article according to the present invention, comprising

[0024] According to a third aspect of the present invention, a polycarbonate composite article according to the present invention is provided for use as an antenna housing.

[0025] The polycarbonate composite article according to the present invention can achieve improved signal penetration performance, dimensional stability, and weight reduction by combining a foamed polycarbonate layer and a non-foamed polycarbonate film layer. Brief explanation of the drawing

[0026] The present invention is described in more detail below with reference to the attached drawings. FIG. 1 shows a schematic diagram of a polycarbonate composite article according to one embodiment of the present invention, wherein (10) represents a non-foamed polycarbonate film layer and (20) represents a foamed polycarbonate layer. Specific details for implementing the invention

[0027] Detailed description of the invention

[0028] Some specific embodiments of the present invention will now be described with reference to the drawings for the purpose of example rather than limitation.

[0029] The descriptions of the various features in this application may be combined with one another where there is no contradiction, and all fall within the scope of protection claimed in this application.

[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by a person skilled in the art to which the present invention pertains. In the event that a definition of a term in this specification conflicts with the meaning commonly understood by a person skilled in the art to which the present invention pertains, the definition set forth herein shall prevail.

[0031] According to the first aspect of the present invention,

[0032] Opaque expanded polycarbonate layer; and

[0033] It comprises a non-foamed polycarbonate film layer on a foamed polycarbonate layer, and

[0034] Here

[0035] The expanded polycarbonate layer comprises polycarbonate resin, an impact modifier, and an optional flame retardant, and

[0036] The non-foamed polycarbonate film layer comprises a polycarbonate resin and an optional UV stabilizer, and has a thickness of 0.2 to 1.0 mm;

[0037] The ratio of the thickness of the non-foamed polycarbonate film layer to the thickness of the foamed polycarbonate layer is in the range of 1:3 to 1:20;

[0038] A polycarbonate composite article is provided that does not contain an inorganic reinforcing material.

[0039] FIG. 1 shows a schematic diagram of a polycarbonate composite article according to one embodiment of the present invention, wherein (10) represents a non-foamed polycarbonate film layer and (20) represents a foamed polycarbonate layer. FIG. 1 should be understood as being used for illustrative purposes rather than for limitation.

[0040] Expanded polycarbonate is opaque. According to the present invention, the opacity is defined as each material having a light transmittance according to EN ISO 13468-2:2006 of less than 5%, preferably less than 1%, most preferably less than 0.1%, measured at a layer thickness of 10 mm.

[0041] Preferably, the thickness of the expanded polycarbonate layer is in the range of 1.5 to 10.0 mm, preferably 2.0 to 6.0 mm, and more preferably 2.0 to 4.0 mm.

[0042] Preferably, the thickness of the non-foamed polycarbonate film layer is in the range of 0.2 to 0.6 mm, for example, 0.2 to 0.5 mm.

[0043] The ratio of the thickness of the non-foamed polycarbonate film layer to the thickness of the foamed polycarbonate layer is important to achieve excellent signal penetration performance.

[0044] Preferably, the ratio of the thickness of the non-foamed polycarbonate film layer to the thickness of the foamed polycarbonate layer is in the range of 1:3 to 1:15.

[0045] A person of ordinary skill in the art can select the type and amount of impact modifiers, flame retardants, and UV stabilizers as needed.

[0046] For example, the impact modifier may be one or more selected from the following: butadiene- or styrene-butadiene rubber substrate and methyl methacrylate-styrene grafted impact modifier (MBS) having a core-shell structure, silicone-acrylate rubber having a core-shell structure, acrylate rubber-substrate core-shell impact modifier, etc.

[0047] Preferably, the butadiene- or styrene-butadiene rubber-based core-shell impact modifier is a butadiene- or styrene-butadiene rubber-based impact modifier grafted with methyl methacrylate or methyl methacrylate-styrene copolymer, for example, Kane Ace M732 available from Kaneka, and Paraloid available from Dow Chemicals. TM These include the EXL2650J, EXL2690, and EXL2691J.

[0048] Suitable siloxane-acrylate rubber having a core-shell structure can be prepared from alkyl methacrylates and / or alkyl acrylates, crosslinking agents, and grafting agents. In this regard, exemplary and preferred alkyl methacrylates and / or alkyl acrylates are C1 to C8-alkyl esters, e.g., methyl esters, ethyl esters, n -butyl ester, tert -Butyl ester, n-propyl ester, n -hexyl ester, n -Octyl ester, n - Lauryl esters and 2-ethylhexyl esters; haloalkyl esters, preferably halo C1 to C8-alkyl esters, e.g., chloroethyl acrylate, and mixtures of these monomers. n-butyl acrylate is particularly preferred.

[0049] Monomers having more than one polymerizable double bond may be used as crosslinking agents for the polyalkyl (meth)acrylate-rubber component of siloxane-acrylate rubber. Preferred examples of crosslinking monomers are esters of unsaturated monocarboxylic acids having 3 to 8 carbon atoms and unsaturated monohydric alcohols having 3 to 12 carbon atoms or saturated polyols having 2 to 4 OH groups and 2 to 20 carbon atoms, e.g., ethylene glycol dimethacrylate, propanediol dimethacrylate, 1,3-butanediol dimethacrylate, and 1,4-butanediol dimethacrylate. These crosslinking agents may be used alone or as a mixture of at least two crosslinking agents.

[0050] Exemplary and preferred grafting agents are allyl methacrylate, trialyl cyanurate, trialyl isocyanurate, or mixtures thereof. Allyl methacrylate may additionally be used as a crosslinking agent. These grafting agents may be used alone or as a mixture of at least two grafting agents.

[0051] Crosslinking agents and grafting agents are present in an amount of 0.1% to 20% by weight based on the total weight of the polyalkyl (meth)acrylate-rubber component of the siloxane-acrylate rubber.

[0052] Desirable siloxane-acrylate rubbers suitable for use include, for example, Metablen S-2100, S-2001, S-2006 available from Mitsubishi Rayon, and Kane Ace MR-01 from Kaneka Corporation.

[0053] Acrylate rubber-based core-shell impact modifiers are available from Dow Chemicals. TM EXL2311, EXL2313, EXL2315, EXL2300, EXL2330, and EXL2390; and Durastrength available from Arkema ® It is preferable that the acrylate rubber-based impact modifier grafted with methyl methacrylate is 410, 440, and 480.

[0054] To improve low-temperature impact resistance, a silicone-acrylate rubber-based core-shell impact modifier is particularly desirable.

[0055] The aforementioned impact modifiers can be used alone or in combination.

[0056] The amount of impact modifier is preferably 1.0% to 8.0% by weight, more preferably 1.0% to 6.0% by weight, and particularly preferably 2.0% to 5.0% by weight with respect to the weight of the foamed polycarbonate layer.

[0057] The flame retardant may be a flame retardant commonly used in the field of polycarbonate materials, such as an organic phosphorus-based flame retardant, such as bisphenol A bis(diphenyl phosphate) (BDP), triphenyl phosphate (TPP), phosphazene, and resorcinol bis(diphenyl phosphate) (RDP).

[0058] The aforementioned flame retardants may be used alone or in combination.

[0059] If present, the flame retardant is preferably present in an amount ranging from 1.0% to 5.0% by weight, more preferably from 1.5% to 3.0% by weight, relative to the weight of the expanded polycarbonate layer.

[0060] The UV stabilizer may be a UV stabilizer commonly used in the field of polycarbonate materials.

[0061] Suitable UV stabilizers are listed in, for example, EP 1 308 084 A1, DE 102007011069 A1, and DE 10311063 A1.

[0062] Particularly suitable UV stabilizers are hydroxybenzotriazoles, e.g., 2-(3',5'-bis(1,1-dimethylbenzyl)-2'-hydroxyphenyl)benzotriazole (Tinuvin® 234, BASF SE, Ludwigshafen), 2-(2'-hydroxy-5'-(tert-octyl)phenyl)benzotriazole (Tinuvin® 329, BASF SE, Ludwigshafen), 2-(2'-hydroxy-3'-(2-butyl)-5'-(tert-butyl)phenyl)benzotriazole (Tinuvin® 350, BASF SE, Ludwigshafen), bis(3-(2H-benzotriazolyl)-2-hydroxy-5-tert-octyl)methane (Tinuvin® 360, BASF SE, Ludwigshafen), 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-(hexyloxy)phenol (Tinuvin® 1577, BASF SE, Ludwigshafen), and also benzophenone 2,4-dihydroxybenzophenone (Chimasorb® 22, BASF SE, Ludwigshafen) and 2-hydroxy-4-(octyloxy)benzophenone (Chimasorb® 81, BASF SE, Ludwigshafen), 2-propenic acid, 2-cyano-3,3-biphenyl, 2,2-bis[[(2-cyano-1-oxo-3,3-diphenyl-2-propenyl)oxy]methyl]-1,3-propanediyl ester (9CI) (Uvinul® 3030, BASF SE, These are 242-hydroxy-4-(2-ethylhexyl)oxy]phenyl-4,6-di(4-phenyl)phenyl-1,3,5-triazine (Tinuvine® 1600, BASF SE, Ludwigshafen) or tetraethyl 2,2'-(1,4-phenylenedimethylidene)bismalonate (Hostavin® B-Cap, Clariant AG). Mixtures of these UV stabilizers may also be used.

[0063] When present, the UV stabilizer is present in an amount ranging from 0.10 wt% to 1.00 wt%, more preferably from 0.10 wt% to 0.50 wt%, and particularly preferably from 0.10 wt% to 0.30 wt% with respect to the weight of the non-foamed polycarbonate layer.

[0064] Preferably, the expanded polycarbonate layer and the non-expanded polycarbonate film layer contain the same polycarbonate resin, so that the adhesion between the expanded polycarbonate layer and the non-expanded polycarbonate film layer is superior.

[0065] In some embodiments, the polycarbonate composite article consists of a foamed polycarbonate layer and a non-foamed polycarbonate film layer.

[0066] In some embodiments, the density of the expanded polycarbonate layer is 0.80 to 1.18 g / cm³ 3 am.

[0067] Lightweight and reduced signal loss can be achieved through cells within the foamed polycarbonate layer.

[0068] A non-foamed polycarbonate film can be placed into a mold cavity and adhered to the inner surface of the mold, and then a polycarbonate composition comprising a polycarbonate resin, an impact modifier, and an optional flame retardant can be injected into the cavity and foamed to form a foamed polycarbonate layer, thereby allowing the polycarbonate composite article according to the present invention to be formed without using additional adhesive.

[0069] Accordingly, in some embodiments, there is no adhesive between the non-foamed polycarbonate film layer and the foamed polycarbonate layer.

[0070] The non-foamed polycarbonate film layer in the polycarbonate composite article of the present invention can satisfy various appearance requirements, such as high gloss and different colors, and different decorative patterns can be realized on the film layer. In addition, the non-foamed polycarbonate film layer can provide water resistance, UV resistance, weather resistance, impact resistance, flame resistance, and other properties as required for application. It can be used outdoors or indoors to meet relevant performance requirements.

[0071] Compared to conventional non-foamed polycarbonate articles having the same thickness, the polycarbonate composite article of the present invention can achieve improved signal penetration performance, better dimensional stability, and lighter weight through a combination of a foamed polycarbonate layer and a non-foamed polycarbonate film layer.

[0072] Signal loss within a medium during electromagnetic wave transmission is influenced by many factors. For a housing serving as a transmission medium, in addition to thickness and the distance from the housing to the antenna, the material's dielectric constant Dk and loss factor Df are two particularly important factors. Dk is a macroscopic physical quantity representing the polarization of the medium, which characterizes its ability to interfere with signal transmission, and its electrical energy storage capacity. Df is a physical quantity representing the dielectric's ability to cause signal loss. The higher the Dk, the higher the Df; this indicates that the medium has a stronger signal transmission blocking ability and experiences greater signal transmission loss. For 5G signals, particularly millimeter waves, the Dk and Df of the antenna housing material need to be reduced to minimize signal loss. When the antenna housing has a two-layer or multi-layer structure, S11 (reflection loss) and S21 (gain) are commonly used indicators to characterize the antenna's transmission performance, as previously mentioned, and their unit is dB.

[0073] Compared to a conventional polycarbonate article having the same thickness, the polycarbonate composite article according to the present invention has relatively low reflection loss (S11) and gain loss (S21).

[0074] According to a second aspect of the present invention, a method for manufacturing a polycarbonate composite article according to the present invention is provided, comprising the following steps:

[0075] A step of placing a non-foamed polycarbonate film on the inner surface of an injection mold and closing the mold to form a cavity; and

[0076] A step of forming a foamed polycarbonate layer by injecting a molten polycarbonate composition comprising a polycarbonate resin, an impact modifier, and an optional flame retardant into a cavity and foaming it.

[0077] Through the above method, design freedom can be achieved. For example, various thicknesses of non-foamed polycarbonate films can be selected, and a foamed polycarbonate layer having a desired thickness, cell size, and density can also be formed by injection foaming.

[0078] A polycarbonate composition comprising a polycarbonate resin, an impact modifier, and an optional flame retardant can be obtained by first mixing polycarbonate pellets with the impact modifier and the optional flame retardant before melting.

[0079] The injection foaming process can be a physical foaming process or a chemical foaming process based on a foaming mechanism. The physical foaming process utilizes physical means to foam plastic. There are mainly two means: the first means involves mixing a supercritical fluid (typically N2 or CO2) with a polymer melt under high pressure to form a single-phase solution; then injecting this single-phase solution into a cavity and causing bubbles to nucleate due to a pressure drop within the cavity to form bubble seeds; as the mold cools, the bubble seeds continue to grow to create an internal bubble structure; and then, after solidification, forming a foamed part having a cell size of approximately 5 to 100 micrometers.

[0080] The second method involves creating a foaming effect by adding hollow spheres to plastic to form a foam.

[0081] Preferably, Trexel's MuCell ®Physical foaming is performed using nitrogen N2 as a supercritical fluid using foaming technology. Nitrogen is the most widely used physical blowing agent. Compared to carbon dioxide (CO2), the dosage of nitrogen (N2) is about 75% lower under the same weight loss conditions. At the same time, nitrogen (N2) can provide a more uniform cell structure and is a stronger blowing agent.

[0082] The chemical foaming process utilizes chemical reactions to generate gas for foaming plastics. Foaming is achieved by introducing a chemical blowing agent into plastic pellets, heating the injection molding barrel, and decomposing the chemical blowing agent through screw shear heat to release gas. Furthermore, foaming can also be achieved by using gas released by chemical reactions between individual components of the plastic composition.

[0083] Chemical foaming agents may be powders or formed foam particles. Particle foaming agents are, for example, XO-331 from Bergen or Hydrocerol from Clariant Company. ® It is possible. In the injection molding process, these cells continue to grow until the mold cavity is completely filled and cooled to form the final cell.

[0084] The injection foaming process can reduce internal stress and deformation of the obtained article. Bubbles grow uniformly throughout the cavity, which can reduce shrinkage of the obtained article. Consequently, the deformation of the formed polycarbonate composite article is significantly reduced, and dimensional stability is excellent.

[0085] Desired weight reduction can be achieved by adjusting injection process parameters.

[0086] The inventors have discovered that a composite article having an isotropic non-foamed polycarbonate film layer and a low-density foamed polycarbonate layer can be used in an antenna housing having sufficient strength, so that a single antenna housing can be used in a wide range of electromagnetic bands.

[0087] Accordingly, according to the third aspect of the present invention, a polycarbonate composite article according to the present invention is provided for use as an antenna housing.

[0088] When a polycarbonate composite article according to the present invention is used as an antenna housing, the non-foamed polycarbonate film layer is an outer layer exposed to the external environment, and the foamed polycarbonate layer is an inner layer close to the antenna.

[0089] The antenna housing according to the present invention can be used as a protective housing for a large outdoor antenna, a small indoor antenna, and an antenna of portable electrical and electronic equipment.

[0090] In particular, the antenna housing according to the present invention can be used as a 5G antenna housing.

[0091] The antenna housing according to the present invention can protect a 5G antenna from the sun, rain and snow, hail and wind after being installed outdoors.

[0092] Polycarbonate composite articles can be designed with desired contours having appropriate sizes for use in many applications, including antenna housings. When used as an antenna housing, the antenna housing may have contours such as a rectangular parallelepiped, cube, semi-ellipse, or hemisphere.

[0093] The non-foamed polycarbonate film layer provides UV resistance and / or impact resistance and prevents moisture from being absorbed into the foamed polycarbonate layer. The presence of moisture can reduce the mechanical and electrical performance of the antenna housing. The non-foamed polycarbonate layer provides structural strength corresponding to the strength and / or stiffness required under expected environmental conditions at the desired installation location of the antenna.

[0094] Compared to conventional polycarbonate antenna housings, the antenna housing according to the present invention can reduce signal loss of electromagnetic waves in the 5G band and can provide a weight reduction of 5% to 20%.

[0095] Examples

[0096] The concept, specific structure, and technical effects of the present invention will be further described with reference to the embodiments, so that a person skilled in the art can fully understand the purpose, features, and effects of the present invention. A person skilled in the art will readily understand that the embodiments of the present invention are for illustrative purposes only and that the scope of the present invention is not limited thereto.

[0097] equipment

[0098] Mucell from Trexel ® An Engel 260-ton injection molding machine with an integrated physical foaming system was used.

[0099] raw material

[0100] Non-foamed polycarbonate films with thicknesses of 0.25 mm, 0.5 mm, 1 mm, and 2 mm, respectively, are from Macrofol by Covestro Polymers (China) Company, Limited ® It is available under the name DE1-4.

[0101] The injection molding raw material for the foamed polycarbonate layer is a polycarbonate composition from Covestro Polymers (China) Company, Limited, which contains 3.5 wt% of Kane Ace MR-01, an impact modifier from Kaneka Corporation, and 2.0 wt% of phosphazene based on the weight of the polycarbonate composition.

[0102] The supercritical fluid is nitrogen (N2).

[0103] measurement

[0104] Tensile modulus and yield stress were tested according to ISO 527-2:2012.

[0105] The dielectric constant Dk and loss factor Df were tested according to ASTM D150 using the 16451B dielectric test facility from Keysight Technologies, where the Keysight resonant cavity method was used in the frequency range of 1.1 GHz to 15.0 GHz and the Keysight waveguide transmission line method was used in the frequency range of 18.0 GHz to 50.0 GHz.

[0106] The simulation process was based on the version of CTS Studio Suite 2014 (CST Microwave Studio) licensed by Southeastern University. In the simulation process, actual material properties were used, for example, copper was used in the metal supply structure. The measured Dk and Df of the non-foamed polycarbonate film and the foamed polycarbonate layer were used as input data for the antenna housing, and the analog output data were S11 and S21. S11 is one of the S parameters representing the reflection loss characteristics. This parameter represents the transmission efficiency of the antenna. The higher the value, the greater the energy reflected by the antenna itself, and the worse the transmission efficiency of the antenna. S21 is the forward transmission coefficient, i.e., the gain value; the higher the value, the better the transmission efficiency of the antenna.

[0107] Comparative Example 1 (CE1)

[0108] A molten polycarbonate composition not containing supercritical fluid is injected into a mold cavity, with a thickness of 4 mm and 1.2 g / cm³ 3 A non-foamed PC film product having a density was obtained. The injection molding process parameters are shown in Table 1.

[0109] The appearance, mechanical properties, signal transmission performance, and simulation results of the non-foamed PC products are shown in Tables 2 and 3, respectively.

[0110] Comparative Example 2 (CE2)

[0111] A molten polycarbonate composition containing a supercritical fluid (N2) is injected into a mold cavity, and the injection process is adjusted so that a weight reduction of 7 wt% is achieved compared to the non-foamed polycarbonate product obtained in Comparative Example 1, with a thickness of 4 mm and 1.12 g / cm² 3 A foamed polycarbonate product having a density was obtained. The injection foaming process parameters used are shown in Table 1.

[0112] The appearance, mechanical properties, signal transmission performance, and simulation results of the product are shown in Tables 2 and 3, respectively.

[0113] Comparative Example 3 (CE3)

[0114] A molten polycarbonate composition containing a supercritical fluid (N2) is injected into a mold cavity, and the injection process is adjusted so that a weight reduction of 15 wt% is achieved compared to the non-foamed polycarbonate product obtained in Comparative Example 1, with a thickness of 4 mm and 1.02 g / cm² 3 A foamed polycarbonate product having a density was obtained. The injection foaming process parameters used are shown in Table 1.

[0115] The appearance, mechanical properties, signal transmission performance, and simulation results of the product are shown in Tables 2 and 3, respectively.

[0116] Comparative Example 4 (CE4)

[0117] A non-foamed polycarbonate film having a thickness of 2.00 mm was cut and placed on the inner surface of a mold. A molten polycarbonate composition containing a supercritical fluid (N2) was injected into the mold cavity, and the injection process was adjusted so that a weight reduction of 7.5 wt% was achieved compared to the non-foamed polycarbonate product obtained in Comparative Example 1, with a thickness of 4 mm and a g / cm³ 3 A two-layer polycarbonate composite product having an average density was obtained. The injection foaming process parameters are shown in Table 1.

[0118] The appearance, mechanical properties, signal transmission performance, and simulation results of the product are shown in Tables 2 and 3, respectively.

[0119] Example 1 of the present invention (IE1)

[0120] A non-foamed polycarbonate film with a thickness of 0.25 mm was cut and placed on the inner surface of a mold. A molten polycarbonate composition containing a supercritical fluid (N2) was injected into the mold cavity. The injection foaming process was adjusted so that a weight reduction of 7 wt% was achieved compared to the non-foamed polycarbonate product obtained in Comparative Example 1, with a thickness of 4 mm and a yield of 1.12 g / cm³ 3 A 2-layer polycarbonate composite product having an average density was obtained. The injection foaming process parameters are shown in Table 1.

[0121] The appearance, mechanical properties, signal transmission performance, and simulation results of the product are shown in Tables 2 and 3, respectively.

[0122] copy Invention Example 2 (IE2)

[0123] A non-foamed polycarbonate film having a thickness of 0.50 mm was cut and placed on the inner surface of a mold. A molten polycarbonate composition containing a supercritical fluid (N2) was injected into the mold cavity, and the injection foaming process was adjusted so that a weight reduction of 7 wt% was achieved compared to the non-foamed polycarbonate product obtained in Comparative Example 1. 4 mm thickness and 1.13 g / cm² 3 A two-layer polycarbonate composite product having an average density was obtained. The injection foaming process parameters are shown in Table 1.

[0124] The appearance, mechanical properties, signal transmission performance, and simulation results of the product are shown in Tables 2 and 3, respectively.

[0125] Example 3 of the present invention (IE3)

[0126] A non-foamed polycarbonate film having a thickness of 0.25 mm was cut and placed on the inner surface of a mold. A molten polycarbonate composition containing a supercritical fluid (N2) was injected into the mold cavity, and the injection foaming process was adjusted so that a weight reduction of 15 wt% was achieved compared to the non-foamed polycarbonate product obtained in Comparative Example 1. 4 mm thickness and 1.03 g / cm² 3 A two-layer polycarbonate composite product having an average density was obtained. The injection foaming process parameters are shown in Table 1.

[0127] The appearance, mechanical properties, signal transmission performance, and simulation results of the product are shown in Tables 2 and 3, respectively.

[0128] copy Invention Example 4 (IE4)

[0129] A non-foamed polycarbonate film having a thickness of 0.50 mm was cut and placed on the inner surface of a mold. A molten polycarbonate composition containing a supercritical fluid (N2) was injected into the mold cavity, and the injection foaming process was adjusted so that a weight reduction of 13 wt% was achieved compared to the non-foamed polycarbonate product obtained in Comparative Example 1, with a thickness of 4 mm and 1.04 g / cm³ 3 A two-layer polycarbonate composite product having an average density was obtained. The injection molding process parameters are shown in Table 1.

[0130] The appearance, mechanical properties, signal transmission performance, and simulation results of the product are shown in Tables 2 and 3, respectively.

[0131] copy Invention Example 5 (IE5)

[0132] A non-foamed polycarbonate film having a thickness of 1.00 mm was cut and placed on the inner surface of a mold. A molten polycarbonate composition containing a supercritical fluid (N2) was injected into the mold cavity, and the injection foaming process was adjusted so that a weight reduction of 11 wt% was achieved compared to the non-foamed polycarbonate product obtained in Comparative Example 1. 4 mm thickness and 1.07 g / cm² 3 A two-layer polycarbonate composite product having an average density was obtained. The injection foaming process parameters are shown in Table 1.

[0133] The appearance, mechanical properties, signal transmission performance, and simulation results of the product are shown in Tables 2 and 3, respectively.

[0134] Table 1: Process parameters used in Comparative Examples (CE1 to CE4) and Examples of the Present Invention (IE1 to IE5)

[0135]

[0136] Table 2: Characteristics of products obtained in Comparative Examples (CE1 to CE4) and Examples of the Present Invention (IE1 to IE5)

[0137]

[0138] From Table 2, compared to the product prepared in Comparative Example 1 CE1), the PC film-free foamed polycarbonate products prepared from Comparative Example 2 (CE2) and Comparative Example 3 (CE3) can achieve a weight reduction of 7% to 15% by weight, respectively, but there are obvious flow marks on the surface of the product and the mechanical properties are also significantly reduced.

[0139] From Table 2, it can be seen that the two-layer polycarbonate composite products prepared in Example 1 (IE1) and Example 2 of the present invention not only have improved mechanical properties with the same weight reduction as that of Comparative Example 2 (CE2), but also possess excellent product surface quality without surface defects. Compared to the product prepared from Comparative Example 3 (CE3), the two-layer polycarbonate composite products prepared in Examples 3 to 5 of the present invention (IE3 to IE5) have improved mechanical properties. Furthermore, the surface of the polycarbonate composite products obtained in Examples 3 to 5 of the present invention (IE3 to IE5) is smooth, defect-free, and has an excellent appearance.

[0140] Table 3: Dk, Df, S11, and S21 of the products obtained in Comparative Examples (CE1 to CE4) and Examples of the Present Invention (IE1 to IE5)

[0141]

[0142] From Table 3, it can be seen that the two-layer polycarbonate composite products prepared in the embodiments of the present invention (IE 1 to IE 5) have different antenna echoes at different frequencies compared to the product prepared from the comparative example (CE 1). The reflection loss value (S11) of the two-layer polycarbonate composite products prepared in the embodiments of the present invention (IE 1 to IE 5) is relatively lower, and the gain value (S21) is relatively higher, which indicates that the polycarbonate composite article of the present invention has improved signal penetration performance compared to non-foamed polycarbonate products.

[0143] Compared to the product (CE 4) prepared in Comparative Example 4 having a thickness ratio of 1:1 for the non-foamed polycarbonate film layer to the foamed polycarbonate layer, the two-layer polycarbonate composite product prepared in Examples of the present invention (IE 1 to IE 5) having a thickness ratio of 1:3 to 1:15 for the non-foamed polycarbonate film layer to the foamed polycarbonate layer has relatively lower reflection loss (S11) and relatively higher gain (S21) for the antenna at different frequencies, which indicates that the polycarbonate composite article of the present invention has improved signal penetration performance.

Claims

Claim 1 A polycarbonate composite article for an antenna housing comprising: an opaque expanded polycarbonate layer; and a non-expanded polycarbonate film layer on the expanded polycarbonate layer, wherein the expanded polycarbonate layer comprises a polycarbonate resin, an impact modifier, and an optional flame retardant; the non-expanded polycarbonate film layer comprises a polycarbonate resin and an optional UV stabilizer, has a thickness in the range of 0.2 to 1.0 mm, and the ratio of the thickness of the non-expanded polycarbonate film layer to the thickness of the expanded polycarbonate layer is in the range of 1:3 to 1:20, and the polycarbonate composite article does not include an inorganic reinforcing material. Claim 2 A polycarbonate composite article according to claim 1, wherein the thickness of the expanded polycarbonate layer is in the range of 1.5 to 10 mm. Claim 3 A polycarbonate composite article according to claim 1 or 2, wherein the thickness of the non-foamed polycarbonate film layer is 0.2 to 0.6 mm. Claim 4 A polycarbonate composite article according to claim 1 or 2, wherein the content of the impact modifier in the expanded polycarbonate layer is 1% to 8% by weight based on the weight of the expanded polycarbonate layer. Claim 5 A polycarbonate composite article according to claim 1 or 2, wherein the polycarbonate resin used in the expanded polycarbonate layer is the same as that in the non-expanded polycarbonate film layer. Claim 6 A polycarbonate composite article according to claim 1 or 2, wherein the polycarbonate composite article comprises a foamed polycarbonate layer and a non-foamed polycarbonate film layer. Claim 7 In claim 1 or 2, the density of the expanded polycarbonate layer is 0.8 to 1.18 g / cm³ 3 Phosphoric polycarbonate composite article. Claim 8 A polycarbonate composite article according to claim 1 or 2, wherein the ratio of the thickness of the non-foamed polycarbonate film layer to the thickness of the foamed polycarbonate layer is in the range of 1:3 to 1:

15. Claim 9 A method for manufacturing a polycarbonate composite article according to claim 1 or 2, comprising: a step of placing a non-foamed polycarbonate film on the inner surface of an injection mold and closing the mold to form a cavity; and a step of forming a foamed polycarbonate layer by injecting a molten polycarbonate composition comprising a polycarbonate resin, an impact modifier, and an optional flame retardant into the cavity and foaming it. Claim 10 A polycarbonate composite article according to claim 1 or 2, intended for use as an antenna housing. Claim 11 A polycarbonate composite article according to claim 10, wherein the non-foamed polycarbonate film layer is the outer layer exposed to the external environment, and the foamed polycarbonate layer is the inner layer adjacent to the antenna.

Citation Information

Patent Citations

  • Polycarbonate resin foam and polycarbonate resin multi- ply body

    JP2001105557A

  • Thermoplastic resin composition for supercritical foam molding with excellent impact resistance

    JP2015117274A

  • Low loss tri-band protective armor radome

    US20180241119A1